2016
DOI: 10.1007/s10461-016-1594-4
|View full text |Cite
|
Sign up to set email alerts
|

Availability, Accessibility, and Price of Rapid HIV Self-Tests, New York City Pharmacies, Summer 2013

Abstract: We conducted an in-person survey of New York City (NYC) pharmacies to assess the availability, accessibility, and price of the over-the-counter, rapid HIV self-test kit. NYC pharmacies were stratified into high, moderate and low morbidity neighborhoods by the HIV diagnosis rate of the neighborhood in which the pharmacy was located. A random sample of 500 pharmacies was taken [250 from high morbidity neighborhoods (HighMN) and 250 from low morbidity neighborhoods (LowMN)]. Pharmacies were excluded if: closed du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Regarding costs, we found that a majority of participants believed that an acceptable price to pay for an HIV self-test in Canada was between Can $10 and $20. This finding is in line with 3 studies from New York City, where participants felt that an affordable and accessible price point was US $15-$25 (compared with the prevailing US $40) [23-25].…”
Section: Discussionsupporting
confidence: 87%
“…Regarding costs, we found that a majority of participants believed that an acceptable price to pay for an HIV self-test in Canada was between Can $10 and $20. This finding is in line with 3 studies from New York City, where participants felt that an affordable and accessible price point was US $15-$25 (compared with the prevailing US $40) [23-25].…”
Section: Discussionsupporting
confidence: 87%
“…Prior research documents a willingness to self‐test . Nunn and colleagues showed that among the participants surveyed in predominantly African American U.S. neighbourhoods with 3% HIV prevalence, nearly 90% were likely or very likely to accept a free HIV self‐test, and 55% were willing to purchase a test; however, only 23% were willing to pay the market price ($40/test) .…”
Section: Discussionmentioning
confidence: 99%
“…This method is used in the United States (Amazon, Ebay) [37], China (Taobao, Jingdong) [37], and the Netherlands [25]. The third way is from pharmacies, which is done in the United States [38], the Netherlands [25], and the United Kingdom [39]. Although there are a number of ways of getting access to self-test kits, the lack of linkage to counseling, treatment, and care for self-test users who test positive is a concern for various stakeholders [40,41].…”
Section: Discussionmentioning
confidence: 99%